1996
DOI: 10.1210/jcem.81.2.8636295
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and the sleep electroencephalogram across the menstrual cycle in young healthy women.

Abstract: Cyclic changes in hormones, body temperature, and metabolic rate characterize the menstrual cycle. To investigate whether these changes are associated with changes in sleep and the sleep electroencephalogram (EEG), a total of 138 sleep episodes from 9 women with no premenstrual syndrome symptoms were recorded every second night throughout one ovulatory menstrual cycle and analyzed in relation to menstrual phase. Ovulation and menstrual cycle stage were confirmed by measurements of temperature, urinary LH, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
6
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 21 publications
15
133
6
2
Order By: Relevance
“…48.8 years old) with and without insomnia reports that both groups of women experience increased awakenings and arousal during sleep and decreased SWS during the luteal versus the follicular phase. Moreover, in both groups, the sleep spindles in the luteal phase compared with the the follicular phase exhibit marked increases in number, duration and higher EEG spectral frequency (14-17 Hz) [86], which is in agreement with earlier reports in younger women [87,88]. Nevertheless, earlier PSG studies report stability of sleep across the menstrual cycle [89,90].…”
Section: (C) Sex Steroids Influence Sleepsupporting
confidence: 91%
“…48.8 years old) with and without insomnia reports that both groups of women experience increased awakenings and arousal during sleep and decreased SWS during the luteal versus the follicular phase. Moreover, in both groups, the sleep spindles in the luteal phase compared with the the follicular phase exhibit marked increases in number, duration and higher EEG spectral frequency (14-17 Hz) [86], which is in agreement with earlier reports in younger women [87,88]. Nevertheless, earlier PSG studies report stability of sleep across the menstrual cycle [89,90].…”
Section: (C) Sex Steroids Influence Sleepsupporting
confidence: 91%
“…It is unclear whether these sex differences in spindle activity relate to meaningful functional differences or whether they are simply an artifact from differences in skull thickness that amplifies the detection of spindles in women (cite check Dijk et al, 1988). In addition, it has been shown that spindle activity increases during luteal phase compare to follicular phase (Baker at., 2007;Baker et al, 2012, Driver et al, 1996Ishizuka et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These studies, however, did not take gender-differences into account. The reason for the gender-specific changes in the high-frequency spindles in the course of depression is not known, but it might be due to the influence of sex steroids as this frequency range is also mainly affected by the menstrual cycle (Driver et al, 1996) and by sex steroids like progesterone (Friess et al, 1997). As alterations in the concentration of sex steroids are observed during depression (Baischer et al, 1995;Toren et al, 1996), an interaction between endocrine chances and sleep-EEG changes in the course of depression seems likely.…”
Section: Discussionmentioning
confidence: 99%